Advanced Laparoscopic Surgery Techniques and Tips - Katkhouda, Namir; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This second edition of Advanced Laparoscopic Surgery, Techniques and Tips represents a comprehensive description of the current laparoscopic techniques. It supplies surgeons with all the information necessary to successfully accomplish laparoscopic surgery. It is a hands-on manual that helps the surgeon avoid pitfalls and acquire the necessary laparoscopic skills quickly and efficiently. It is a ready source of practical help when trouble-shooting is necessary. Advanced laparoscopic surgery is an excellent merger of a textbook and atlas for the surgeon who wants to extend and refine his laparoscopic techniques.
General concepts -- Cholecystectomy -- Common Bile Duct Exploration and Bilioenteric Anastomoses -- Liver Surgery -- Esophageal Surgery -- Gastric Surgery -- Appendectomy -- Colorectal Procedures -- Small Bowel Obstruction -- Inguinal Hernia Repair -- Laparoscopic Incisional and Ventral Hernia Repair -- Splenectomy (Total and Partial) and Splenopancreatectomy -- Adrenalectomy -- Bariatric Surgery -- Single-Access Laparoscopic Surgery (SALS) -- Advanced Laparoscopic Suturing Techniques -- Index.
Keywords: Medicine; Surgery; Abdomen -- Surgery; Colon (Anatomy) -- Surgery; Endoscopic surgery; Vascular Surgery; Medicine & Public Health; Surgery; Abdominal Surgery; Colorectal Surgery; Minimally Invasive Surgery; General Surgery; Vascular Surgery